Prognostic Factors and Functionality in Metastatic Spinal Cord Compression: Cohort Study - Faria, Eduarda Martins de (2022)
Introduction: Metastatic Spinal Cord Compression (MSCC) has great potential of irreversible loss of motor and sensory function, and it is considered an oncological emergency. Objective: Evaluate the prognosis of MSCC and the functionality of patients with solid tumors. Method: Cohort study was conducted in patients with cancer who developed MSCC between January 2017 and December 2018. Clinical and socio-demographic data were extracted from physical and electronic charts. Survival analysis was performed by the Kaplan-Meier method. Results: The study included 90 patients who were diagnosed with MSCC. At the time of MSCC diagnosis, 55.5% of patients were unable to walk. Patients with MSCC after lung cancer had 4.1-fold more odds of death (95% CI: 1.79-9.41; p=0.001), those with genitourinary tumors, 1.9-fold higher risk of death (95% CI: 1.06-3.45; p=0,02), and with other types of tumors, 3.1-fold higher risk of death (95% CI: 1.58-6.24; p=0.001) when compared with patients with MSCC after breast cancer. Conclusion: The clinical relevance of this study relies on the findings that the primary type of tumor is a predictive factor for overall survival of MSCC. More than half of the patients were unable to walk at the MSCC diagnosis.